Implementasi Dan Peran Manajemen Syariah - Sovy Muti Ardianty Hasibuan; Chuzaimah Batubara (LPPM Universitas Labuhanbatu, 2025)
Islam as a perfect system of life certainly has an idea about the concept of control. Since the field of management is very important from the point of view of economic life, Islam dictates the actual management process. This is because many people believe that they have a fanatical view of what management really means. From a competitor's perspective, the Islamic Control Industry does not expect its competitors to lose or lose. However, there is a concept that every company can drive improvement without eliminating competitors. Competitors are not enemies who must be eliminated, but partners who are involved in the success of activities carried out in the field. Implementation of administrative functions based on Islamic sharia values.